2018
DOI: 10.1111/apt.14811
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Asia‐Pacific consensus recommendations on endoscopic tissue acquisition for biliary strictures

Abstract: These consensus statements provide evidence-based recommendations for endoscopic tissue acquisition of biliary strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 97 publications
1
48
0
Order By: Relevance
“…Given the limited sensitivity of BC and FB and in order to avoid false negative results, it is recommended either to use an alternative method like EUS-FNB for tissue sampling 5,6 or to repeat the ERC with FB/BC (supplemented if necessary with advanced imaging techniques like cholangioscopy or intraductal ultrasound). Our findings support the latter recommendation: Taking into account an inevitable patient drop-out due to the clinical course of malignant disease, confirmation of stricture dignity through other modalities or a loss of follow-up, repetition of tissue sampling via ERC led to satisfying NPVs (with the 4 th ERC yielding an NPV of 88.89%, see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the limited sensitivity of BC and FB and in order to avoid false negative results, it is recommended either to use an alternative method like EUS-FNB for tissue sampling 5,6 or to repeat the ERC with FB/BC (supplemented if necessary with advanced imaging techniques like cholangioscopy or intraductal ultrasound). Our findings support the latter recommendation: Taking into account an inevitable patient drop-out due to the clinical course of malignant disease, confirmation of stricture dignity through other modalities or a loss of follow-up, repetition of tissue sampling via ERC led to satisfying NPVs (with the 4 th ERC yielding an NPV of 88.89%, see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic or percutaneous fine needle biopsy is a viable option in case of a visible mass or bile duct wall thickening 12 14 ; but most patients with IBiS suffer from cholestasis or even septic cholangitis and require biliary drainage preferably through ERC. In this situation according to current recommendations 4 , 6 transpapillary BC or FB is the primary method to obtain tissue for a cytological or histological diagnosis. While the specificity of both methods is excellent, sensitivity and NPV are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that the performance of cholangioscopy for proximal biliary strictures and EUS-tissue acquisition for distal biliary strictures had high sensitivities of 92.3% (95%CI: 74.9−99.1) and 96.0% (95%CI: 79.7−99.9), respectively. However, despite the high accuracy, EUS-tissue acquisition of a primary bile duct tumor is currently contraindicated in patients who are potential candidates for liver transplantation [21].…”
Section: Biliary Stricturesmentioning
confidence: 99%
“…It was found that SOC had a sensitivity of 77.8% compared to 51.1% for ERCP. In 2018 a consensus document was published [21], aiming to provide evidence-based guidance to assist the selection of tissue diagnostic tools and improve the diagnostic yield for biliary strictures. This document supports that the selection of tissue diagnostic tools for biliary strictures depends on the clinical setting, tumor location and the availability of expertise.…”
Section: Biliary Stricturesmentioning
confidence: 99%